‘’Evaluation of Flora Bacteria Grown in Blood Cultures: Are They Etiologic Agent of Infection or Only Contaminants?’’ (Bangladesh Journal of Medical Science, 2021)
Objective: In this study, it was aimed to determine whether the flora bacteria growing in blood cultures were infectious agents or only contaminants, for this purpose the hemogram parameters and other demographic characteristics of the patients were evaluated.Materials and Methods: We evaluated 11.579 blood culture results using the BacT/ALERT® microbial detection system. The skin flora bacteria was detected in the blood cultures during one year and the rates of infectious agents among these bacteria were investigated retrospectively. The blood culture results, which were accepted as true bacteremia and contamination were compared in terms of positive blood culture flask count and inflammation markers (white blood cell count, neutrophil ratio, lymphocyte ratio and C-reactive protein levels).Results: The total number of blood culture test was 11.579. Out of this number, 8205 (70.87%) was free of microbial growth and there was 3374 (29.13%) with microbial growth. 2609 (77.3%) of the positive cultures represented skin flora bacteria, 2510 (96.2%) of them were coagulase negative staphylococci. Only 50 (1.9%) of the flora bacteria were considered as infectious agents in terms of clinical and laboratory findings in addition to culture. A statistically significant correlation was found between true bacteremia and white blood cell (WBC) count and C-reactive protein (C-RP) levels (p